Wind Turbine Rotor Simulation via CFD Based Actuator Disc Technique Compared to Detailed Measurement - Mahmoodi, Esmail; Jafari, Ali; Keyhani, Alireza (Center of Biomass & Renewable Energy, Diponegoro University, 2015)
In this paper, a generalized Actuator Disc (AD) is used to model the wind turbine rotor of the MEXICO experiment, a collaborative European wind turbine project. The AD model as a combination of CFD technique and User Defined Functions codes (UDF), so-called UDF/AD model is used to simulate loads and performance of the rotor in three different wind speed tests. Distributed force on the blade, thrust and power production of the rotor as important designing parameters of wind turbine rotors are focused to model. A developed Blade Element Momentum (BEM) theory as a code based numerical technique as well as a full rotor simulation both from the literature are included into the results to compare and discuss. The output of all techniques is compared to detailed measurements for validation, which led us to final conclusions.